2011
DOI: 10.1074/jbc.m111.251728
|View full text |Cite
|
Sign up to set email alerts
|

Human Siglec-5 Inhibitory Receptor and Immunoglobulin A (IgA) Have Separate Binding Sites in Streptococcal β Protein

Abstract: Sialic acid-binding immunoglobulin-like lectins (Siglecs) are receptors believed to be important for regulation of cellular activation and inflammation. Several pathogenic microbes bind specific Siglecs via sialic acid-containing structures at the microbial surface, interactions that may result in modulation of host responses. Recently, it was shown that the group B Streptococcus (GBS) binds to human Siglec-5 (hSiglec-5), an inhibitory receptor expressed on macrophages and neutrophils, via the IgA-binding surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…The IgA-binding M4 and non-IgA-binding M4Δ451 were diluted in 10 mM sodium acetate (pH 4) (Merck, Darmstadt, Germany) and immobilized via amine coupling on separate CM5 sensor chip chambers (GE Healthcare, Uppsala, Sweden) at moderate response levels (1500 response units) as previously described (44). A flow chamber subjected to the immobilization conditions but without addition of protein was used as a control (blank) for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The IgA-binding M4 and non-IgA-binding M4Δ451 were diluted in 10 mM sodium acetate (pH 4) (Merck, Darmstadt, Germany) and immobilized via amine coupling on separate CM5 sensor chip chambers (GE Healthcare, Uppsala, Sweden) at moderate response levels (1500 response units) as previously described (44). A flow chamber subjected to the immobilization conditions but without addition of protein was used as a control (blank) for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Several serotypes of the group B Streptococci (serotypes Ia, Ib, II and V) are known to produce the Streptococcus β protein [13], which binds SHP-2 directly. SHP-2 binds to the Nterminal part of Streptococcus β protein (AA 1-152, called B6N region); this region is sufficient to trigger recruitment of SHP-2 to Siglec-5 (tested using the human monocyte cell line U937) [14]. Exact role of SHP-2 in the Streptococcus β protein signaling is poorly understood; use of the isogenic β-negative group B Streptococcus mutant revealed that the Streptococcus β protein interaction with host Siglec-5 recruits SHP-2 to Siglec-5 in U937 cells, inhibits phagocytosis of group B Streptococci by U937 cells, inhibits the IL-8 secretion of primary human neutrophils, and suppresses also the oxidative burst of primary human neutrophils and formation of neutrophil extracellular traps in response to the group B Streptococci [14].…”
Section: Streptococcal β Protein Recruits Shp-2mentioning
confidence: 99%
“…Selected inhibitors of non-metazoan PTPs:(12) benzanilide scaffold-based compound,(13) isoxazole carboxylic acid isostere 433 Da analogue,(14) brunsvicamide B, (15) brunsvicamide C,(16) iodoacetamide, (17) N-ethylmaleimide,(18)(19) isothiazolidinone derivatives, (20) nitrophenylphosphate derivative, (21) bidentate α-ketoacid-based compound, (22) salicylic acid derivative, (23) homotyrosine-based selenic acid.…”
mentioning
confidence: 99%
“…GBS MVs contained multiple virulence factors, including: 1) HylB, 2) CAMP factor (Christine, Atkins, Munch-Peterson factor [85]), a secreted pore-forming protein [86] that may amplify [87], but is not essential for GBS virulence [88], 3) IgA binding protein, with the ability to bind human IgA [89] for host immune evasion [90] and 4) multiple enzymes that may regulate ECM degradation [84]. Intra-amniotic administration of GBS MVs in pregnant mice caused significant damage to choriodecidual tissues and stimulated leukocytic infiltration and inflammation, leading to membrane weakening [84].…”
Section: Bacterial Factors That Promote Gbs Vaginal Colonization Ascmentioning
confidence: 99%